Network advantage for a commune – case study - Flieger, Marcin (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The main purpose of the article is to analyze the characteristics of network advantage gained by communes, including the dynamic perspective of achieving another levels of network cooperation maturity. Network advantage constitutes the main benefit from network cooperation for a knot and it can be perceived as a determinant of an organization’s collaborative advantage. Thus, at the beginning the author identified key benefits typical for network cooperation, both at the network level and the knot level. As the scrutiny included a dynamic perspective, also the level of network cooperation maturity were identified. This theoretical background allowed carrying research in a form of a case study. It showed sorts of network advantage gained by the commune, as the network cooperation maturity increased. The results led to conclusions concerning the range and characteristics of achieved benefits, which allows thorough understanding of the phenomenon and more effective creation of a commune’s collaborative advantage.